Large Tunable 16-Tupled Millimeter Wave Generation Utilizing Optical Carrier Suppression With a Tunable Sideband Suppression Ratio - Asha,; Dahiya, Sandeep (Frontiers in Physics, 2021)
Coping up with the rising bandwidth demands for 5G ultra-high speed applications, utilizing millimeter (MM) wave spectrum for data transmission over the radio over a fiber-based system is the ideal approach. In this study, a highly conversant and spectrally pure photonic generation of a 16-tupled MM wave signal using a series-connected DD-MZM with a lower modulation index, a splitting ratio, and a wider tunable range is presented. A 160-GHz MM wave is generated through a double sideband optical carrier suppression technique having an optical sideband suppression ratio (OSSR) of 69 dB and a radio frequency sideband suppression ratio (RSSR) of 40 dB. However, the OSSR and the RSSR are tunable with values greater than 15 dB when the modulation index (M.I.) varies from 2.778 to 2.873, ±8° phase drift, and a 15-dB enhancement in the OSSR with a wider nonideal parameter variation range giving acceptable performance can be seen in the model as compared with previous research works.